ChemInform Abstract: Stereoconvergent Arylations and Alkenylations of Unactivated Alkyl Electrophiles: Catalytic Enantioselective Synthesis of Secondary Sulfonamides and Sulfones. Issue 12 (March 2015) - Choi, Junwon; Martin‐Gago, Pablo; Fu, Gregory C.
Abstract Nickel‐catalyzed stereoconvergent Negishi arylations and alkenylations of racemic α‐bromosulfones and ‐sulfonamides are described.